Olor a claustro imaginarios sociales (2005)
Daily life in the city is so ordinary that most of the time we pass by many important influences on our lives without noticing. We are in permanent contact with people, things or places and keep memories through sensorial perception without noticing how much they affect us. The least noticed sense in our perception is smell, but it allows us to implement relationships between people, things and events, that help to create and recreate images of our cities through the concept of social imaginaries. Using the sense of smell a social imaginary is created around university life, making the five years of a professional course into a specific representation of space, time and place.